Experimental studies on the Acute Toxicity of Bos taurus.Ursus thibetanus extract solution(BU) for Herbal-acupuncture - Soh, Kyung-Sun; Jeong, Chang-Gil; Lee, Sang-Woon; Park, Pyung-Mo; Kim, Jae-Hyung; Kang, Dae-In; Jo, Hoo-Lee; Kim, Kwang-Ho (Korean Pharmacopuncture Institute, 2001)
This experiment was carried out to study on the safety assessment of Bas tures . Ursus thibetanus extract solution(BU) for Herbal acupuncture. SD rats and ICR mice were used for acute toxicity test the results were summerized as follows; 1. In rats and mice, LD50 value could not be measured. 2. There were no abnormal finding in acute toxicity test treated BU for Herbal-acupuncture.